2018
DOI: 10.1055/s-0038-1667184
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Stress Urinary Incontinence in Women: A Systematic Review and Meta-analysis

Abstract: Objective To compare surgical treatments for stress urinary incontinence in terms of efficiency and complications. Data Sources We searched the MEDLINE and COCHRANE databases using the terms stress urinary incontinence, surgical treatment for stress urinary incontinence and sling. Selection of Studies Forty-eight studies were selected, which amounted to a total of 6,881 patients with scores equal to or higher than 3 in the Jadad scale. Data Collection Each study was read by one of the authors, added to a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 76 publications
0
8
0
2
Order By: Relevance
“…A meta-analysis of colposuspension and MUS demonstrated significantly higher overall and objective cure rates with MUS but a higher risk of bladder perforation in retropubic slings as compared to TOT. 8 A regional study from Turkey showed that TOT is associated with improved objective cure rates of SUI and QOL. 9 Similarly a local study from Pakistan revealed that TVT is an effective and safe procedure for the surgical treatment of SUI.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of colposuspension and MUS demonstrated significantly higher overall and objective cure rates with MUS but a higher risk of bladder perforation in retropubic slings as compared to TOT. 8 A regional study from Turkey showed that TOT is associated with improved objective cure rates of SUI and QOL. 9 Similarly a local study from Pakistan revealed that TVT is an effective and safe procedure for the surgical treatment of SUI.…”
Section: Introductionmentioning
confidence: 99%
“…Em uma revisão sistemática com metanálise englobando 16 estudos totalizando 2646 mulheres, as taxas de cura objetiva e subjetiva nos casos de IUE foram equivalente quando comparados os sling RP e TOT (OR 1,07, IC 95% 0,68-1,68) e a cura subjetiva no grupo transobturador (TOT) em comparação com a do grupo RP também não foi estatisticamente significante (OR 1,05, IC de 95% 0,37-2,99) (SUN et al, 2015). Uma revisão sistemática de 48 estudos com metanálise totalizando 6.881 pacientes que o sling RP foi superior ao sling TOT quanto as taxas de cura objetiva (RC: 1,27; IC95%:1,05 -1,54) e subjetiva (RC:1,23; IC95%1,02-1,48) (OLIVEIRA et al,2018).…”
Section: Discussionunclassified
“…Although some published studies have described persistent pain in the groin or thigh after placement of transobturator MUS, passing or transient pain is more common, occurring in 5% to 31% of patients. These results can be partially attributed to the fact they were reported in studies of personal series with short follow‐up times; pain is more common in the first 2 weeks, affecting 30% of patients but diminishing significantly at 6 months, and more specifically 5.1% in TOT and 3.1% in TVT patients, and only requiring pharmacological analgesia in 1% of cases . Infection is rare, affecting less than 1.6% of all cases .…”
Section: Introductionmentioning
confidence: 91%
“…These results can be partially attributed to the fact they were reported in studies of personal series with short follow-up times; pain is more common in the first 2 weeks, affecting 30% of patients but diminishing significantly at 6 months, and more specifically 5.1% in TOT and 3.1% in TVT patients, and only requiring pharmacological analgesia in 1% of cases. [18][19][20] Infection is rare, affecting less than 1.6% of all cases. 15 The complication rate has been shown to vary according to the experience and the learning curve of the surgeon, this being a determining factor in these cases.…”
Section: Introductionmentioning
confidence: 99%